Perancangan Aplikasi Berbasis GUI dalam Pengelolahan Citra Gambar Kulit Buah Kelapa Sawit Dengan Metode Konvolusi - Dian Kurnia (CV MEDAN TEKNO SOLUSI, 2024)
Image convolution is a technique for smoothing an image or clarifying an image by replacing pixel values with a number of pixel values that match or are adjacent to the original pixels. This study discusses the design of a program for processing images using the Convolution method, which consists of the Gaussian blur, prewitt, image sharpening (sharpen) and sobel algorithms. But with the convolution, the size of an image that has been processed with the Convolution method remains the same, the size of the image does not change. The application designed to apply the convolution method uses Matlab R2009b software, where each image will be processed convolutionally with a choice of Gaussian blur, prewitt, image sharpening (sharpen), and sobel algorithms. Then the previous image size will be compared with the results of the image that has been processed with the Convolution method, so that it is expected that even though there is a pixel conversion that occurs, the image size will be the same, and image changes only occur in the color display of the image.